2012
DOI: 10.1111/j.1751-7133.2011.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Improves Heart Rate Variability in Older Patients With Heart Failure: A Randomized, Controlled, Single‐Blinded Trial

Abstract: Background Reduced heart rate variability (HRV) in older patients with heart failure (HF) is common and indicates poor prognosis. Exercise training (ET) has been shown to improve HRV in younger patients with HF. However the effect of ET on HRV in older patients with HF is not known. Methods and Results Sixty-six participants (36% males), age 69±5 years, with HF and both preserved ejection fraction (HFPEF) and reduced ejection fraction (HFREF), were randomly assigned to 16 weeks of supervised ET (ET group) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 39 publications
(90 reference statements)
3
45
0
Order By: Relevance
“…HRV reflects beat-to-beat changes in heart rate (HR), expressing the sympathovagal interaction obtained by the variation of both instantaneous HR and R-R intervals within the cardiac cycle [4]. Lower variance in HRV might be explained by either lower parasympathetic or higher sympathetic activity, and has been associated with the development of pathological conditions such as metabolic syndrome [5], stroke [6], chronic fatigue [7,8], obesity [9,10], and especially hypertension [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRV reflects beat-to-beat changes in heart rate (HR), expressing the sympathovagal interaction obtained by the variation of both instantaneous HR and R-R intervals within the cardiac cycle [4]. Lower variance in HRV might be explained by either lower parasympathetic or higher sympathetic activity, and has been associated with the development of pathological conditions such as metabolic syndrome [5], stroke [6], chronic fatigue [7,8], obesity [9,10], and especially hypertension [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, obese adolescents may exhibit increased heart rate and cardiac output at rest, as well as decreased baroreflex sensitivity and higher blood pressure [14][15][16]. The assessment of autonomic activity in obese adolescents is therefore clinically relevant, and HRV indices are frequently used as markers of sympathetic and parasympathetic modulation [2,6]. Evidently, it is important that the results obtained from HRV are accurate and reliable, truly reflecting the modulation of autonomic nervous system activity to the heart.…”
Section: Introductionmentioning
confidence: 99%
“…22 Published data indicated that exercise training restores ANS function by increasing vagal tone and decreasing sympathetic activity which lead to parasympathetic-sympathetic balance improvement in CHF patients. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]…”
Section: Exercise Training and Hrvmentioning
confidence: 99%
“…Several trials examined the influences of physical activity on HRV. The enhancing effect of training on HRV was observed in healthy participants as well as in coronary artery disease, heart failure, obesity, type-2 diabetes mellitus and following myocardial infarction [9,10]. In healthy participants, baseline autonomic status has been shown to be an important determinant of cardiac autonomic response to exercise [11].…”
Section: Introductionmentioning
confidence: 97%